RELIGIOUS ETHICS EDUCATION OF MUSLIM AND BUDDHIST FAMILIES IN WATAMPONE - Afifuddin Afifuddin; Muhammad Alqadri Burga (Al-Qalam, 2022)
This paper examines the phenomenon of religious ethical education in Moslem and Buddhist families in the city of Watampone. This study aims to reveal the family behaviors in carrying out efforts to internalize the values of religious ethics in the scope of the family, especially children. In this case, the researcher focuses on the Moslem and Buddhist families, in order to find the multicultural and inclusive-based substance and formulation of inter-religious ethic education. This research is qualitative descriptive with phenomenological approach and using comparative method. Researchers found that the most essential thing in religious ethics education in the family is exemplary and good advice. Buddhist families in Watampone undertake ethical education with the application of the Majjima Patipada as a path to holiness, avoiding the bad kamma to attain nibbana. While the Moslem family paid great attention to aspects of worship and good manners (akhlaq mahmudah)